Dowling-Degos disease. Case report with a study of the family tree. - Regazzini, R.; De Filippi, C.; De Giulio, R.; Rosso, R.; Donadini, A. (European Journal of Pediatric Dermatology, 2018)
A 13-year-old girl in perfect health presented with brownish, confluent and in some sites papillomatous maculo-papular lesions. The lesions involved the neck, the face, the axillary folds and partially the trunk. A lesion of the trunk showed on light microscopy an acanthotic proliferation of the epidermal crests, which branched out in the papillary dermis. The epidermal crests originated from the epidermis and even from the covering epithelium of the piliferous infundibula. Melanic deposits were mainly located on the basal layers and were not associated with increased junctional melanocytes. The clinical features, the pathological findings and the laboratory examinations led to the diagnosis of Dowling-Degos disease. The study of the farnily tree unveiled other two cases of the same disease in the father and in the paternal grandmother of the patient. Finally the problems of differential diagnosis with other pigmentary disorders were discussed, taking into account the wide clinical spectrum of Dowling-Degos disease.